HUBUNGAN KONSEP DIRI TERHADAP KECEMASAN PADA IBU HAMIL TRIMESTER TIGA MENGHADAPI PERSALINAN DI WILAYAH KERJA PUSKESMAS WONOSOBO 1 - Wulan Tri Mulyani; Wiwin Renny Rahmawati; Angga Sugiarto; Lulut Handayani (Jurnal Ilmu Keperawatan Maternitas, 2022)
Background: Pregnancy is the period from conception until the fetus is born. During pregnancy, a mother experiences physical and psychological changes, with these changes a mother will from her self-concept, self-concept indirectly affects the occurrence of anxiety in pregnant women such as worry and fear of childbirth. Purpose: this study to determine the relationship between self-concept and anxiety in third trimester pregnant women facing childbirth in the work area Puskesmas Wonosobo 1. Method: This research used cross sectional correlation research design. The sampel in the study amounted to 58 pregnant women. Data collection technique by means of total sampling. A tool to measure self-concept using a questionnaire adapted from previous research and anxiety using hamilton anxiety rating scale (HARS) questionnaire. Statistical test using the spearman test. Result: shows the results of significance of 0,000 (p<0,05), which means there is a relationship between the self-concept to anxiety third trimester pregnant women facing childbirth.